Vat-photopolymerization of ceramic materials: exploring current applications in advanced multidisciplinary fields - Fiume, Elisa; Coppola, Bartolomeo; Montanaro, Laura; Palmero, Paola (Frontiers in Materials, 2023)
Additive manufacturing has brought about a real revolution in the manufacture of objects in a variety of application areas, overturning the traditional paradigm based on subtractive approaches. The potential benefits deriving from the application of these techniques in the field of ceramic materials extend to different industrial sectors, leading to shorter, more accurate and cost-effective manufacturing processes. Within the present review, we provide a transversal analysis of the state-of-the-art of the applications of vat-photopolymerization technologies, namely stereolithography and digital light processing in relevant technological industrial/research fields of our times, including biomedicine, energy, environment, space and aerospace, with a special focus on current trends and project-specific requirements. Unmet challenges and future developments will be discussed as well, providing readers a transfer of knowledge and "lessons learned" from one field to the other, being this approach aimed at the further growth of the technology towards its industrialization and market uptake.This is a provisional file, not the final typeset article Table 1. Classification of advanced ceramics according to their characteristics and main applications. Class Characteristics Applications examples Ref. Structural ceramics Enhanced mechanical properties under demanding conditions Adiabatic diesel turbine and automotive engines Aerospace systems Heat exchangers Electronic devices Medical devices (*) Cutting tools Metal machining Military devices (Schoenung, 2001) Electro-ceramics Piezoelectric, ferroelectric or dielectric response High-capacity dielectric devices Non-volatile memories (DRAMs) Energy storage and conversion